Effects of Different Resistance Exercise Forms on Body Composition and Muscle Strength in Overweight and/or Obese Individuals: A Systematic Review and Meta-Analysis - Liu, Xinhong; Gao, Ye; Lu, Jiandong; Ma, Qirui; Shi, Yajun; Liu, Jingqi; Xin, Shuai; Su, Hao (Frontiers in Physiology, 2022)
Purpose: This paper is a systematic review and meta-analysis to determine the effects of different forms of resistance training on body composition and muscle strength in overweight and/or obese people. Method: Only randomized controlled trials (RCTs) were included by searching relevant databases such as web of science, PubMed, and EBSCO, with search dates up to September 30, 2021. These trials performed resistance exercise training in overweight and/or obese people, and outcome indicators included evaluation of body composition and muscle strength, among other relevant indicators. The Cochrane evaluation tool was used to evaluate the methodological quality of the included literature, and statistical analysis was performed using R analysis software. Results: Fifteen studies, 18 trials, with a total of 669 participants meeting eligibility criteria were included in the final analysis which included three resistance training types (own body weight, resistance bands, free weight). The results showed that resistance bands improved body fat (SMD -0.79, 95% CI -1.25 to -0.33, I2=0%) in overweight or obese people better than other resistance training types. Own body weight resistance training was better for increasing skeletal muscle mass in overweight or obese people (SMD 0.48, 95% CI 0.04 to 0.92, I2=0%). In addition, for muscle strength increase, although resistance exercise was shown to improve muscle strength, there was no significant difference between the three exercise forms compared. Conclusion: Resistance bands can improve body composition by reducing BF. Resistance bands can improve body composition by reducing BF, while it is more effective in increasing muscle mass and own body weight. Therefore, for overweight and obese people, resistance bands resistance exercise can be taken for fat loss, and resistance exercise for own body weight for further muscle gain and maintenance of muscle mass, so as to achieve the purpose of improving body composition.